Water Pollution as a Threat to Physical Health and Cognitive Development During Childhood: An Analytical Theoretical Review (Al-Farooq Journal of Sciences, 2026)
Drinking water quality is a fundamental determinant of public health and healthy development during childhood. Children are particularly vulnerable to environmental contaminants because childhood is characterized by rapid physical, neurological, and cognitive development. The risks associated with water pollution are no longer limited to waterborne diseases; scientific evidence suggests that exposure to certain chemical and biological contaminants may be associated with adverse nutritional, physical, neurological, cognitive, and behavioral outcomes in children.This paper aims to review and analyze the scientific evidence concerning the effects of water pollution on physical health and cognitive development during childhood, with particular emphasis on contaminants of public health concern, including arsenic, lead, manganese, fluoride, nitrates, per- and polyfluoroalkyl substances (PFAS), and microbial contaminants. The study adopts a descriptive-analytical approach through an analytical theoretical review of relevant scientific literature, focusing primarily on studies published between 2019 and 2026, while drawing on selected earlier foundational references when necessary.The reviewed evidence indicates that unsafe water may affect children through multiple pathways. Microbial contamination is associated with gastrointestinal disease, diarrhea, impaired nutritional status, and growth disturbances, whereas exposure to certain chemical contaminants and heavy metals has been associated with a range of neurological, cognitive, and behavioral outcomes. The magnitude of these associations varies according to contaminant type, concentration, timing and duration of exposure, nutritional status, and accompanying environmental and social conditions. The literature also reveals persistent research gaps concerning chronic exposure, contaminant mixtures, long-term developmental outcomes, and evidence from low-resource settings.The paper concludes that protecting children from water pollution requires an integrated preventive approach involving continuous drinking-water quality monitoring, reduction of pollution sources, early identification of hazardous contaminants, strengthened public-health awareness, and collaboration among health, environmental, and educational sectors. Further longitudinal and context-specific research is also needed to clarify the long-term developmental consequences of water contamination during childhood.
Keywords: Water pollution; Childhood; Physical health; Cognitive development; Water contaminants; Public health